Debunking the myth of job fit in higher education and student affairs - Reece, Brian J.; Tran, Vu T.; DeVore, Elliott N.; Porcaro, Gabby; Quaye, Stephen John, 1980- (Stylus Publishing, LLC, 2019)
Co-published with This groundbreaking book examines a concept that has gone unexamined for too long: The concept of "job fit" in the student affairs profession. Fit is a term used by nearly everyone in student affairs throughout the hiring process, from search committees and hiring managers to supervisors and HR professionals. This book opens a conversation about the use of "job fit" as a tool for exclusion that needs to be critically investigated from multiple standpoints.This edited collection brings together a number of voices to look at the issues involved through various lenses to explore the ways policies, procedures, environments, and cultural norms provide inequitable job search experiences for individuals from various marginalized groups. These include looking at the legal aspects, employer definitions, communication barriers, as well as scholarly personal narratives looking at the concept from the perspective of class, race, gender and sexual orientation.Emerging from the Commission for Social Justice of ACPA, the personal narratives and critical explorations in this book are an attempt to provide graduate students and professionals with a resource that is relevant to the job search in an increasingly competitive job market, while taking into account the complex realities of their identities. The normative assumptions of "fit" are analyzed by the authors to make visible the barriers those assumptions create for those with non-dominant identities.The student affairs profession strives for inclusion and acceptance as a core value, and an essential competency. The profession has made progress in the way it serves students, but there is a disconnect between the conversation about students and the way those same values play out in the treatment of practitioners and scholars in the field. This book aims to help job seekers looking to evaluate fit in their current and possible future positions, as well as hiring managers who face challenges in creating equitable hiring processes.Challenging the norms and rhetoric about job fit in student affairs means that scholars and practitioners alike must be able to incorporate this topic explicitly into various aspects of the profession.